The effect of various forms of selenium supplied to pregnant goats on selected blood parameters and on the concentration of Se in urine and blood of kids at the time of weaning - A. Pechova; L. Sevcikova; L. Pavlata; R. Dvorak (Veterinární Medicína, 2012)
The aim of this trial was to compare the effect of supplementation of goats with different forms of selenium on the metabolism of their kids at the time of weaning. The experiment was performed with 45 kids of mothers supplemented with various forms of selenium. Group C was control while the other four groups were supplemented with selenium for six weeks before (0.3 mg/goat/day) and after parturition (0.9 mg/goat/day). Group Se-I received sodium selenite while the other groups received organic forms: Se-lactate-protein complex (Se-L), Se-proteinate (Se-P) and Se-yeast (Se-Y). The kids were weaned at three months of age and samples of blood and urine were taken. Parameters monitored in the blood included Se, glutathione peroxidase (GPx), Zn, Cu, thyroxine, triiodothyronine, protein, immunoglobulins, muscle enzymes, total antioxidant status, vitamin A and E. Se levels were determined In the urine. Selenium supplementation of goats from six weeks before delivery significantly influenced selenium concentrations in the blood of kids. Significant differences (P < 0.0002) were found between the control and all experimental groups and further between Se-Y and the other experimental groups (Se-Y: 243.0 ± 20.3 μg/l; Se-I: 156.3 ± 34.3 μg/l; Se-P: 152.6 ± 41.5 μg/l; Se-L: 146.7 ± 20 0 μg/l; C: 67.6 ± 13.1 μg/l). The highest concentration was found in the group supplemented with Se-yeast with a high content of selenomethionine. The other two organic forms of selenium (proteinate and lactate-protein complex) increased the concentration of Se in blood and the activity of GPx to the same extent as the inorganic form of selenium. Se supplementation did not have a negative effect on the concentration of copper and zinc in the blood serum of kids, but we found decreased concentrations of thyroxine in the experimental groups (Se-Y: 79.8 ± 12.8 nmol/l; Se-I: 66.5 ± 13.2 nmol/l; Se-P: 76.2 ± 25.7 nmol/l; Se-L: 84.5 ± 14.8 nmol/l; C: 92.7 ± 13.4 nmol/l). Significant differences were found between the group C and groups Se-I and Se-P (P < 0.05). The supplementation of mothers with Se both in organic and inorganic forms was sufficient to prevent Se deficiency in kids at the time of weaning.